1995
DOI: 10.1111/j.1365-246x.1995.tb06445.x
|View full text |Cite
|
Sign up to set email alerts
|

3-D density model for the lithosphere of Europe: construction method and preliminary results

Abstract: S U M M A R YA map of the observed gravity field of Europe has been constructed by averaging anomalies on a 1" X 1" grid in a combined reduction of Bouguer anomalies on land and free-air anomalies offshore. On the basis of the observed gravity field and recent seismic data on crustal structure, a 3-D density model for the lithosphere of Europe has been calculated. The model is represented by two complementary parts, each obtained by its own specific method. For the south of Eastern Europe, the 3-D density mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Regions of relatively light upper mantle have been distinguished beneath the eastern and northwestern parts of the East European Platform. A heavier upper mantle has been outlined below the Alps, the Calabrian Arc, the Caucasus and the South Caspian Depression (Yegorova et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Regions of relatively light upper mantle have been distinguished beneath the eastern and northwestern parts of the East European Platform. A heavier upper mantle has been outlined below the Alps, the Calabrian Arc, the Caucasus and the South Caspian Depression (Yegorova et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It was proved that density anomalies in the crust are compensated by the upper mantle in all geotectonic units studied except in the Alpine Belt. With the observed correlation between gravity effect of the crust and traveltimes of P ‐waves to the Moho boundary (Yegorova et al 1995), the distribution of residual gravity anomalies of mantle origin (without direct gravity effect calculations) has been obtained. Comparing the latter with both the data on velocity heterogeneities in the upper mantle and the distribution of terrestrial heat flow, we concluded a density decrease of the upper mantle below most of Western Europe and the existence of high density domains in the lithosphere below the Caucasus—South‐Caspian region and the Alps (Yegorova et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect caused by these crustal factors creates small local anomalies. We therefore presume that large residual anomalies are caused mainly by mantle heterogeneities (YEGOROVA et al, 1995).…”
Section: Modelling Resultsmentioning
confidence: 98%
“…The map uses Bouguer anomalies on land and free-air anomalies offshore, averaged over a 1°×1°grid. Portion of the map of Europe and North Atlantic (YEGOROVA et al, 1995). Contour interval 10 × 10 −5 m s −2 .…”
Section: Structure Of the Model And Initial Datamentioning
confidence: 99%
See 1 more Smart Citation